Human-wildlife interaction, conflict, and coexistence: Bibliometric analysis from Scopus (1987–2023) - Guzman Valqui, Betty Karina; Silva López, Jhonsy O.; Rojas Briceño, Nilton B. (Malque Publishing, 2025)
Human interactions with wildlife range from conflict (negative) to coexistence (positive or neutral). The scientific interest in this topic is increasing rapidly, although the terminology used varies among authors. This study presents a bibliometric analysis of literature on human–wildlife interaction, conflict, and coexistence (HWCICx) from 1987 to October 2023 using Scopus data analyzed with VOSviewer and the Bibliometrix package in R. An exponential rise in publications was identified between 1995 and 2022, confirming HWCICx as an emerging yet robust research field. The United States and the United Kingdom lead in publication volume and international collaboration, whereas researchers from Asia and Latin America show growing involvement. Journals specializing in ecology, conservation, and wildlife, such as Biological Conservation, Oryx, and Human–Wildlife Interactions, dominate the field, although newer specialized journals are gaining visibility. Predominant research topics include carnivore–livestock conflicts and species conservation. However, new areas of interest are emerging, including urban wildlife interactions and the sociocultural aspects of coexistence. This study offers an updated overview of the evolution of HWCICx research and highlights the need for integrated natural and social science approaches to develop sustainable models of coexistence.